The effect of dyslexia on information retrieval: A pilot study - MacFarlane, Andrew; Al-Wabil, Areej; Marshall, Chloe Ruth; Albrair, A.; Jones, Susan A.; Zaphiris, Panayiotis (My University, 2010)
Purpose: The purpose of this paper is to resolve a gap in the knowledge of how people with dyslexia interact with information retrieval (IR) systems, specifically an understanding of their information-searching behaviour. Design/methodology/approach: The dyslexia cognitive profile is used to design a logging system, recording the difference between two sets of participants: dyslexic and control users. A standard Okapi interface is used - together with two standard TREC topics - in order to record the information searching behaviour of these users. Findings: Using the log data, the differences in information-searching behaviour of control and dyslexic users, i.e. in the way the two groups interact with Okapi, are established and it also established that qualitative information collected (such as experience etc.) may not be able to account for these differences. Evidence from query variables was unable to distinguish between groups, but differences on topic for the same variables were recorded. Users who view more documents tended to judge more documents as being relevant, in terms of either the user group or topic. Session data indicated that there may be an important difference between the number of iterations used in a search between the user groups, as there may be little effect from the topic on this variable. Originality/value: This is the first study of the effect of dyslexia on information search behaviour, and it provides some evidence to take the field forward.
Keywords: Behaviour; Dyslexia; Information retrieval; User interfaces